Territorial Development Policy : A Practitioner's Guide - Lall, Somik V. (World Bank, Washington, DC, 2013)
Policymakers in developing countries are increasingly recognizing the necessity of developing strategies and identifying specific investment programs to reduce spatial differences in living standards within their national territories. Choosing among alternate policy instruments to support spatial convergence is not straightforward. Should the focus be social policies that support human development in lagging regions and promote migration to leading regions? Or infrastructure policies that connect lagging regions with markets in leading ones? Or investment and regulatory policies to create new clusters of economic activity in regions not favored by the market? The 2009 World Development Report (WDR) provides a policy framework for integrating lagging and leading areas within countries, prioritizing and sequencing policy instruments based on the severity of the territorial integration challenge. To operationalize the WDR's policy priorities, this report discusses analytic tools to measure the magnitude of regional disparities and identify where and in what activities specific policies and investments can be most effective. It also highlights potential economic and social tradeoffs of alternative policy instruments for pursuing spatial equity. Country case studies are provided to illustrate how these tools either inform a specific policy debate on territorial development or have been directly used to guide ongoing policy discussions between the Bank and counterparts in national and sub national governments.